زيادة الطاقة الحرارية للأفران الشمسية باستخدام العاكس ذو الواجهة الشمالية - تقلا, جوني; صبيح, مسعود; حسن, هيام (Latakia University Journal -Engineering Sciences Series, 2019)
إن توفير الطاقة وتلبية الطلب المتزايد عليها يعد مشكلة اقتصادية واستراتيجية الآن وفي المستقبل لجميع دول العالم، فهي مشكلة حاضرة ومقلقة للدول المستوردة للنفط، وأيضا لها هاجسها الكبير للدول النفطية من منطلق محدودية الاحتياط النفطي. لذلك لابد من البحث عن مصادر بديلة للطاقة التقليدية، إن أهم هذه المصادر تعد الطاقة الشمسية، طاقة الشمس الحرارية واستخدامها في مجال الطهي والطبخ من خلال الأفران الشمسية سيكون موضوع هذا البحث. تهدف هذه الدراسة الى تحسين الأداء الحراري للفرن الشمسي المجهز بعاكس مفرد ذي واجهة جنوبية من خلال إضافة عاكس ذي واجهة شمالية. تم إجراء الدراسة بشكل تحليلي أو رياضي وأيضا تجريبي. الدراسة التحليلية تمثلت بإعداد النمذجة الرياضية للفرن الشمسي بعاكس مفرد ذي واجهة جنوبية ثم التوصل الى الأداء الحراري بعد إضافة العاكس ذي الواجهة الشمالية. شملت الدراسة التطبيقية إجراء بعض الاختبارات على أداء الفرن الشمسي ذي العاكس المفرد ومقارنته مع الفرن الشمسي بعاكس مزدوج. The issue of providing and filling the increased demands for energy is considered an economic and strategic present and future problem for all countries of the world. It is an existing and annoying problem for oil-importing and oil-exporting countries due to limited oil reserve. Consequently, there is a great need to search for substitute sources for traditional energy, the most important of which is solar energy, the thermal energy of the sun and using it in cooking by using sun ovens. This study deals with the issue of improving the thermal performance of the sun oven fitted with a southward single reflector by adding an extra northward reflector. Throughout this study, we apply analytical or mathematical methods in addition to using an experimental one. The analytical study caters for preparing the mathematical modelling of the sun oven fitted with a southward reflector. We have maintained the thermal performance after adding a northward reflector. The applied part of this study is based on conducting certain experiments on the performance of the sun oven fitted with an individual reflector and comparing it with the sun oven fitted with a double reflector.